Executive coaching impact on leader development in a South African bank - Phungula., Sandile M. (My University, 2017)
ABSTRACT This case study was conducted within a South African bank and it seeks to add value in the overall skills development fraternity within a South African context, particularly in leader development. The aim of this research was to investigate and evaluate the impact of executive coaching in developing leaders of a South African bank using Kirkpatrick’s evaluation model. The data was collected through face-to-face interviews within a South African bank where the questions were semi-structured to allow for flexibility in the direction of the conversations. There were a total of fourteen respondents that included six divisional executives, two managing executives, five executive coaches and one executive coach coordinator. There were three key findings of the study that were consistent with literature, namely, i.) Executive coaching has a positive impact in developing leaders in a South African Bank and this was the general view from different executive coaches’ perspectives. In the main, it is the emotional competence or at least, self-awareness created which benefits the executives, not just in their professional, but also in their personal lives; ii.) the Kirkpatrick evaluation model can be used to measure the impact of executive coaching with few reservations within level two and three. iii.) There were three key cases presented by the respondents showing financial benefits from the executive coaching in the bank. Overall, all the participants shared their moving experiences and it was clear that there are some critical gains that are priceless and can never be measured in any financial currency.
M.B.A. Thesis
Keywords: Executive coaching, Leadership -- South Africa.